Pengembangan Manual Book Boneka Tangan Berkarakter dengan Model Tadzkirah untuk Menumbuhkan Nilai-Nilai Karakter Positif Anak Usia Dini - Ridwan, Ridwan; Wulansari, Widi (Efektor, 2019)
Character education can succeed optimally, character education is prepared at an early stage, infrastructure, and appropriate learning methods. Character education is not only the responsibility of the teacher but also the responsibility of all elements of society. The selection of appropriate learning media will influence the results achieved. One of the right media that is used to grow the character values ​​of children's character is puppets character with the help of the method of storytelling and is completed with a manual book. The method in this research is development research to advocate learning from Kemp combined with the Borg and Gall models. The manual book (handbook) of hand puppets with the tadzkirah model is validated by 3 validation experts namely experts in science, learning experts and instructional media experts. The trial run is limited to 2 (two) field tests. The results of this study are hand puppet manuals that are suitable for use as a means of growing the positive character values ​​of young children. The results of field trials prove the increase in knowledge and understanding of story content that will foster positive character values ​​of early childhood